Implementasi Pemeliharaan Otonom untuk Pengendalian Kualitas dalam Proses Slitting di PT Lami Packaging Indonesia - Magfirotulhayat Magfirotulhayat; Muhamad Irpan; Rizky Faturohman; Safitri Rosiana (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research aims to determine the results of the effect of implementing AM (Autonomous Maintenance) on the AZ7 and T2D machine slitting process at the PT factory. Lami Packaging Indonesia addresses production downtime by setting new cleaning standards and standard inspections. The method used in solving problems using the Autonomous Maintenance (AM) method aims to increase the knowledge, responsibility and skills of production operators related to machines, so that productivity will increase overall.